Analysis of the effects of supplementation of certain antioxidants on adjustive cancer treatment (Research, Society and Development, 2020)
Objective: To present an analysis of the effect of supplementation of certain antioxidants on adjuvant cancer treatment. Methodology: This is an integrative literature review conducted through the databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO) and Medical Literature Analysis and Retrieval System Online (MEDLINE). Results: Twenty-seven articles were selected. After analyzing the inclusion and exclusion criteria, only seven were part of the final research sample. According to the results found, regarding breast cancer GLN antioxidants (15gs / day) do not offer protection against systemic or local oxidative stress. Noting also that the consumption of antioxidant vitamins A, C and E by this population is below the necessary, and these are primordial during chemotherapy treatment. For the 2-methoxyestradiol (2-ME) and Resveratrol compounds, effective antimelanoma agents have been shown. The antioxidant effects of Libidibia ferrea extract on adjuvant treatment of colorectal cancer have important effects. Already the aqueous extract of Carya illinoinensis in relation to its antioxidant effects, it is likely that cell infeasibility and antiproliferative activity are dependent on different types of phenolic compounds. Conclusion: This research proves to be of great relevance since it presents positive results regarding treatment as well as cancer prevention. The bottom line is that further in-depth studies regarding the effectiveness of antioxidants in adjuvant cancer treatment are needed, as studies such as these are scarce in the literature.